Pengembangan Konservasi dan Edukasi TOGA Refugia melalui Kearifan Lokal Teh Djamu Refugia (TEDJAFU) Desa Jatirejoyoso, Kepanjen - IzmatulIza, Amal; Patimah, Anggi Siti; Puspitasari, Cindy Kharisma (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The Toga Refugia Conservation Development Program Based on Green Economy through the Local Wisdom of Tea and Djamu Refugia was implemented in Jatirejoyoso Village. Jatirejoyoso Village has the potential for toga refugia plants which are deliberately grown as natural IPM. In fact, toga refugia has many benefits for the body, but the use of toga refugia is not yet optimal. The methods used in implementing the program include community assistance, the formation of POKJA nurseries and TEDJAFU MSMEs, cleaning, mapping and nurseries on conservation land, TOGA refugia processing training classes, as well as the opening of TOGA Refugia Conservation Area Tourism. The result is the transformation of the Refugia Jati Park into a TOGA Refugia Cultivation Area as a solution for toga conservation, the development of the TEDJAFU product as a solution for utilizing TOGA refugia which produces three products in the form of brewed tea, tea bags and herbal medicine. Apart from that, this program can increase community knowledge about the toga refugia plant and can also improve the village economy.